2022
DOI: 10.1093/nutrit/nuac034
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nutritional status at the time of stroke on adverse outcomes: a systematic review and meta-analysis of prospective cohort studies

Abstract: Context and Objective:The impact of existing malnutrition on stroke outcomes is poorly recognised and treated. Evidence was systematically reviewed and quantified by meta-analysis. Methods: MEDLINE, EMBASE and Web of Science were searched from inception to 11 January 2021 and updated in July. Prospective cohort studies, in English, evaluating anthropometric and biomarkers of nutrition on stroke outcomes were included. Risk of bias was assessed using the Scottish Intercollegiate Guidelines Network checklist. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 51 publications
2
27
1
Order By: Relevance
“…The importance of nutritional management after stroke is well recognized by most relevant guidelines, which generally recommend early screening for dysphagia and malnutrition and the consideration of oral nutritional supplements for patients who are malnourished or at risk of malnourishment ( 50 55 ). These recommendations are supported by a recent meta-analysis concluding that impaired nutritional status on admission is associated with poor functional recovery and increased mortality ( 56 ). The lower levels of many nutritional compounds as found in current study may result in suboptimal substrate availability for numerous structural and functional recovery processes after stroke.…”
Section: Discussionmentioning
confidence: 94%
“…The importance of nutritional management after stroke is well recognized by most relevant guidelines, which generally recommend early screening for dysphagia and malnutrition and the consideration of oral nutritional supplements for patients who are malnourished or at risk of malnourishment ( 50 55 ). These recommendations are supported by a recent meta-analysis concluding that impaired nutritional status on admission is associated with poor functional recovery and increased mortality ( 56 ). The lower levels of many nutritional compounds as found in current study may result in suboptimal substrate availability for numerous structural and functional recovery processes after stroke.…”
Section: Discussionmentioning
confidence: 94%
“…Another important component of the HALP score, hemoglobin and albumin, is also strongly associated with stroke prognosis. Patients with anemia or hypoalbuminemia have a higher risk of stroke, cardiovascular disease and mortality [31,32] . Curtelin et al [33] reported that in low hemoglobin or further declined hemoglobin leads to worsening neurological function in AIS, speci cally probably because of lower hemoglobin levels with altered cerebral hemodynamics leading to worsen of ischemia and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Search terms across the included reviews were broadly similar with "body mass index" and "stroke" being widely used. Six of the included reviews reported on post-stroke mortality 2,[4][5][6]11,12 and five reported on post-stroke functional recovery. [2][3][4][5]12 All included reviews reported findings according to PRISMA guidelines.…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%
“…[2][3][4] This phenomenon counterintuitively indicates that stroke survivors who are overweight have better mortality and functional outcomes following a stroke, compared to normal weight. [2][3][4][5] Although much of the literature has focused on the effects of being overweight on post-stroke outcomes, it is notable that people who are underweight (BMI < 18.5 kg/m 2 ) appear to be worse off compared to people of normal weight, with an increased risk of mortality 2,[4][5][6] and reduced functional capacity [2][3][4][5] after a stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation